The transformation of the case system in African Latin as evidenced in inscriptions - Adamik, Béla (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
Present paper intends to explore the process of the transformation of the case system as evidenced in the inscriptions of the Roman provinces Africa Proconsularis and Numidia. First the peculiarities of the transformation of the case system in African Latin in the preChristian and Christian periods will be analysed. Then the African distributional patterns of case system changes will be compared to those of other regions of the Empire selected for the survey including Spain, Gaul (including Germany), Italy, Illyricum, and the city of Rome. Finally, the results of the present analysis, especially those regarding the dialectological positioning of Roman Africa, will be compared with the results of the investigation of Gaeng 1992 regarding the later, Christian period.